Agricultural dust explosions in 2014 - Ambrose, R. P. Kingsly (Kansas State University. Dept. of Grain Science and Industry, 2015)
There were seven dust explosions reported in the U.S. in 2014 according to Kingsly Ambrose, Assistant Professor, Kansas State University. This compares to 7 in 2013 and a ten-year average of 10.0 explosions.
Keywords: Grain dust; Dust explosions